Two new species of the genus Pholcus (Araneae: Pholcidae) from Taihang Mountains, China, with first report of the female of Pholcus oculosus - Peng, Yanqiu; Zhang, Feng (Entomologica Fennica, 2011)
Two new species of the genus Pholcus from Taihang Mountains, China, are reported: Pholcus papilionis sp. n. and P. suboculosus sp. n. The female P. oculosus Zhang & Zhang, 2000 is reported for the first time.